The Role Of Relationship Marketing, Word Of Mouth, Customer Delight In Building Customer Satisfaction And Loyalty : Systematic Literature Review - Muhammad Luthfi Alif Utama; Agung Winarno; Heri Pratikto (Dinasti International Journal of Education Management And Social Science, 2025)
The dynamics of consumer behavior in the development of technology and information makes consumer customers have greater access to information and communication channels in referencing what they want and a deep understanding of how various elements. Customers have become very active in choosing what they need and sorting out what they want. This literature study describes the Role of Relationship Marketing Variables, Word Of Mouth, Customer Delight in building Customer Satisfaction And Loyalty whose purpose is to understand how these various elements influence each other in the modern marketing context. 200 articles found through the Publish Perish journal search tool, the Google website with Scopus indexed journal searches, with a combination of Copernicus indexed journal searches, Sinta, local Indonesian and foreign journals. After that, identify relevant literature with the results of 30 relevant articles in the review and discussion. The analysis in this journal is Descriptive analysis, where the results of the literature review are grouped with several categories and then discussed and analyzed descriptively. With the adoption of modeling using the PRISMA Flow Diagram tool. The results of the study conducted that. The result is that all the results of the Journal Literature Review carried out use quantitative research types with data analysis carried out using SEM PLS 22 Journals. Multiple Regression Analysis 5 Journals. Meanwhile, exploratory analysis factors, content analysis techniques, non-experimental and crosssectional each 1. In general, the results of the journal review research conducted by examining the role of each variable and looking for the influence of Relationship marketing variables, Word Of Mouth, Customer Delight in building Customer Satisfaction and Customer Loyalty have an influence between variables. The rest of the research shows different results with the results of negative and insignificant influence between variables.